Different Background and Situation of US and China Bring Different Opinions about Video Games - Yang, Chengzhi (Transactions on Social Science, Education and Humanities Research, 2024)
With the booming of technology development, video games gradually became a kind of common way to relax. Nowadays cellphones and laptops are generalizing, and video games’ quality has become better than before. Video games seem to be a necessity in people’s daily life, especially the teenagers and the young. This study works on different environments between the US and China leading to the differences in video game development and people’s perspective towards it. The environment is composed of countless elements. This study will focus mainly on education, institutions, and gaming companies in these two different countries. The totally different education, policy, and companies will bring different opinions about video games. The purpose of the study is to compare the differences and seek both benefits and disadvantages of each side. These facts shape the parents from these two countries to have quite different opinions about video games. Compared to Us parents, China parents’ attitudes are relatively serious towards video games and think it will bring more negative influences. US parents are relatively open to video games. Also, the different environment causes teenagers in China may be more obsessed with video games than Us teenagers.